EXAMINING ABLEIST NARRATIVES: MEDIA PORTRAYALS OF DISABILITY AND CONTROVERSIES IN MALAYALAM CINEMA - K S, Anjana; Banerjee, Sarbani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concepts such as ‘normal’, ‘normalcy’ and ‘able-bodied’ set the parameter in an able-society to evaluate a person’s ability and disability. The ableist conscious inherent in the representation of the disabled in Malayalam cinema has been celebrated in the early 1990s to the end of 2010s, and the auteurs of the film themselves claim that their films support the community through these representations. Disability depictions often vacillate between a comic interlude, underplayed heroism, liability and burden (Menon, Neelima 1). There has always been a conflict between the representation of the disabled through the ableist lens and their question of identity. Even when the representations occur, it connotes the successful life of the able-body. The climax sequence of Athbhutha Dweepu (2005) and the disabled protagonist’s soliloquy is one such of a kind. There have been many stigmas and stereotypes associated with disability that are inherent in the ableist consciousness; they are portrayed in several television programs that tend to promote charity model of disability and often blends it with inspiration-porn. The film Kaduva (2022) was scrutinized highly in recent times, due to its insensitive comment on the birth of the disabled children and deeds of their parents. The continued discussions on the online platforms and several posts from the parents of the disabled forced the aforementioned film’s team to appear before the public to apologize for the comment. The profound implications of the prevalence of normalcy have a significant impact on the very essence of cultural production. Characters with disabilities consistently carry ideological significance, as do instances of illness or accidents that alter these characters. The paper aims to examine ableist memes disseminated through social media platforms, distinguishing between ableism and disablism. It broadly investigates the media’s handling of the Kaduva issue and various instances in television programs to analyse the perpetuation of stigma and the construction of normalcy.